Regional anesthesia for acute and subacute orthopedic trauma: A review - Nina D. Fisher; Andrew S. Bi; Uchenna O. Umeh; Ansara M. Vaz; Kenneth A. Egol (Health Sciences Review, 2022)
Pain management in the setting of acute and subacute orthopedic trauma can be challenging. Due to the recent focus on the rising opioid epidemic, as well as the adverse side of effects of opioid pain medication, multimodal pain control has become the standard of care for management of orthopedic trauma, particularly during operative fixation. The purpose of this paper is to report on the use of regional anesthesia for surgical intervention of extremity fractures in patients who present following traumatic injury as part of a multimodal pain management protocol. Types of, indications for, and outcomes of both upper and lower extremity peripheral nerve blocks will be reviewed.